Essential fashion illustration digital - Streeter, Loreto Binvignat; Safari eBooks (Beverly, Mass. : Rockport Publishing, 2010)
Essential Digital Fashion Illustration' is a complete, in-depth tutorial that guides readers step-by-step through the digital techniques typically employed in fashion design and illustration.
Description based on print version record.
Keywords: Fashion drawing -- Data processing; Computer drawing -- Data processing; Adobe Photoshop; Adobe Illustrator (Computer file); Electronic books